Analysis of the Effect Emotional Intelligence on Understanding Level in Programming Algorithm Learning - Sri Handani Widiastuti; Nur Imansyah; Abdul Zain (Journal of Systems Engineering and Information Technology (JOSEIT), 2023)
The course Algorithms and Programming in the Informatics Engineering study program is given in the first and second semesters, as this course is a scientific course that serves as a basis for advanced programming courses in higher semesters. It is often the case that intelligent graduates obtain good academic grades during their studies and become outstanding students, but when working in their field of expertise, their performance is not as good as graduates who had lower academic grades. Success is not only determined by intellectual intelligence (IQ), but also by other types of intelligence. Intellectual intelligence or cognitive intelligence is one type of intelligence, while non-intellectual intelligence includes other types of intelligence outside of cognitive intelligence. One of this non-intellectual intelligence is emotional intelligence. Intellectual intelligence and non-intellectual intelligence play equally important roles in supporting individual success. This research discusses the analysis of the effect of emotional intelligence on the level of understanding of algorithms and programming using the linear regression method implemented with an application. The sample taken is students of the Informatics Engineering study program in the third and fourth semesters. With the results of the influence of emotional intelligence on the understanding of Algorithms and Programming, it can provide a solution to improve students' understanding of the Algorithms and Programming course and other computer courses in the scientific field of the Informatics Engineering study program. The application is created using the Python programming language.